POTENSI LULUSAN PROGRAM STUDI ILMU PERPUSTAKAAN SEBAGAI PENDAMPING PENGEMBANGAN PEMBERDAYAAN KELUARGA - Elnumeri, Farli; Amelia, Sandra (Association of Indonesian Library and Information Professionals, 2018)
This research has purposed to see the opportunities of developing information services for the public with zero budgets available to deploy professionals. When the capability of library science graduate has questioned; especially for providing information services that require by the society and about the dedication they have to actively support family empowering program through ?Pos Pemberdayaan Keluarga/Posdaya? (Family Empowering Centre). This research will describe the strategy and action undertakes to achieve the effectiveness of information services given towards society information needs. This research has applied exploratory methods that rely on researcher observation towards the object, as mentioned is ?Pos Pemberdayaan Keluarga?. The library has been built as local awareness and initiatives. The usefulness of ?Pos Pemberdayaan Keluarga? could be indicated through the library achievement towards the target program. Librarian or library science graduate who involved in ?Pos Pemberdayaan Keluarga? has developed information in some range of services such as reference services. It includes the development of information re-packaging, Pathfinder, training and workshop and holding some sharing session for society. Furthermore, the librarian or library science graduate aimed to have the ability to responding to community needs as well as develop the library through a government program and capability development.